Atividade física e sintomas depressivos em cuidadores de idosos com demência de Alzheimer - Golfeto, Gabrielle Morel [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The Alzheimer's dementia (AD) is a chronic, neurodegenerative and progressive disorder, characterized by cognitive decline, affecting brain functions like memory, reasoning and communication, occurrence of behavioral disturbances and difficulty in performing activities of daily living (ADLs). These conditions lead to patient’s dependence, which can cause depressive symptoms in caregivers, due to physical and mental burden caused by of the difficulties of the act of caring. Whereupon, it became necessary to find strategies to improve the caregivers’ quality of life. An interesting hypothesis is that physical activity can be considered a non-pharmacological alternative in reducing depressive symptoms, being an important factor for maintaining the physical and mental well-being of the general population, especially on positive changes in mood and social interaction. This study aimed to analyze the effects of a physical activity protocol on depressive symptoms and burden of caregivers of patients with AD. This experimental study, of longitudinal character, comprised a sample of 19 caregivers, of both genders, divided into two groups: a) intervention group – IG (10 caregivers who participated in a physical activity protocol) and b) control group – CG (9 caregivers who didn’t participate in the physical activity protocol). This protocol, which worked the components of functional ability and social interaction of participants, was held three times a week, being 48 sessions of 60 minutes each, for 16 weeks. Data collect was performed at pre and post-intervention for both groups. The assessment instruments used were: a) Zarit Burden Interview, b) Hospital Anxiety and Depression Scale (HAD) and c) battery of motor tests of the American Alliance for Health Physical Education Recreation and Dance (AAHPERD). Nonparametric statistics was used, with intra-group comparison by Wilcoxon test... (Complete abstract click electronic access below)

A demência de Alzheimer (DA) é uma doença crônica, neurodegenerativa e progressiva, que se caracteriza por declínio cognitivo, afetando funções corticais como memória, raciocínio e comunicação; ocorrência de distúrbios de comportamento e dificuldade para realizar as atividades de vida diária (AVDs). Estas condições levam à dependência do paciente, que pode provocar o aparecimento de sintomas depressivos no cuidador, devido à sobrecarga física e psíquica decorrente das dificuldades advindas do ato de cuidar. Diante disso, tornou-se necessário pesquisar estratégias que melhorem a qualidade de vida dos cuidadores. Uma hipótese interessante é a de que a atividade física pode ser considerada uma alternativa não-farmacológica na redução de sintomas depressivos, por ser um fator importante para a manutenção do bem-estar físico e mental da população em geral, principalmente no que diz respeito às alterações positivas no humor e na interação social. Assim, o objetivo deste estudo foi analisar os efeitos de um protocolo de atividade física nos sintomas depressivos e na sobrecarga de cuidadores de pacientes com DA. O estudo, de caráter longitudinal, foi constituído por uma amostra de 19 cuidadores, de ambos os gêneros, distribuídos em dois grupos: a) grupo intervenção – GI (10 cuidadores que participaram de um protocolo de atividade física) e b) grupo controle – GC (9 cuidadores que não participaram do protocolo de atividade física). Este protocolo, que trabalhou os componentes de capacidade funcional e a interação social dos participantes, foi realizado três vezes por semana, totalizando 48 sessões de 60 minutos cada, durante um período de 16 semanas. A coleta de dados foi realizada nos momentos pré e pós–intervenção, para ambos os grupos. Os instrumentos de avaliação utilizados foram:... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Educação fisica; Educação física adaptada; Cuidador; Alzheimer's dementia; Caregiver; Depressive symptoms; Burden; Physical activity